International counterterrorism law - Casey-Maslen, Stuart (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2024)
"International Counterterrorism Law explains clearly and with real-life examples showing how the law criminalizes acts of terrorism. It looks at terrorism in peacetime and in armed conflicts over the past fifty years. It is of interest to lawyers and non-lawyers alike"-- Provided by publisher.
Defining terrorism in international law -- The key components of international counterterrorism law -- National terrorism legislation worldwide -- Prosecution of terrorism suspects in domestic courts -- Counterterrorism action under international law -- Prosecution of terrorism as an international crime -- State responsibility for terrorism -- The outlook for international counterterrorism law.
BIBINDX
Keywords: Terrorism -- Prevention -- Law and legislation; Terrorism (International law)